Relative Permeability Measurements during the Exsolution and Dissolution of Hydrogen Gas Produced by the Hydrolysis of Sodium Borohydride - Mohammed, O. (2020)
The presence of trapped gas in otherwise water‐saturated porous media has a substantial effect on water flow, which is important to a wide variety of subsurface applications including groundwater remediation, CO2 sequestration, and the release of greenhouse gases associated with oil and gas development. Trapped gases can be created by external drainage and imbibition, where fluids invade from system boundaries, or by internal drainage (exsolution), where gas is produced at nucleation sites within a porous medium. A series of laboratory experiments were conducted in thin flow cells, in which H2 gas was produced by the reaction of sodium borohydride and water to produce a range of trapped gas saturations. Aqueous relative permeability was measured following H2 exsolution and during dissolution and compared with measurements in the presence of air trapped by external drainage and imbibition. The results showed that gas saturations higher than those produced by external displacement remained trapped (immobile) when produced by exsolution but that aqueous relative permeability was similar at the same gas saturations. The results of this study suggest that traditional aqueous relative permeability relationships based on external drainage may be suitable to describe the effects of internal drainage in uniform, loosely packed sands. However, additional investigation across a wider range of porous media and at higher gas saturations is required.